(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Marketing research is the scientific and systematic way of gathering, analyzing, and distributing non-routine marketing information that aids marketers in solving marketing problems. Through the controlled process, it addresses the marketing problems and analyzes every factor that has a positive or adverse effect on marketing activities.